2015
DOI: 10.1161/circulationaha.115.015279
|View full text |Cite
|
Sign up to set email alerts
|

Does Timing of Coronary Artery Bypass Surgery Affect Early and Long-Term Outcomes in Patients With Non–ST-Segment–Elevation Myocardial Infarction?

Abstract: Background-Current guidelines do not provide recommendations for optimal timing of coronary artery bypass surgery (CABG) in patients with non-ST-segment-elevation myocardial infarction. Our study aimed to determine the impact of CABG timing on early and late outcomes in patients with non-ST-segment-elevation myocardial infarction. Methods and Results-A total of 758 patients underwent CABG within 21 days after non-ST-segment-elevation myocardial infarction between January 2008 and December 2012 at our instituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 26 publications
1
25
0
4
Order By: Relevance
“…It has become clear that the incidence of stroke per se is higher among patients with AMI, presumably due to the increased systemic inflammatory state . Although PCI‐focused AMI trials reported cerebrovascular event rates between ≈0.3% and 1%, stroke risks among AMI patients undergoing CABG range between 0.8% and 6% . We found a slightly although not statistically significant lower proportion of strokes in patients with STEMI compared with NSTEMI (2.0% versus 3.9%, P =0.134).…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…It has become clear that the incidence of stroke per se is higher among patients with AMI, presumably due to the increased systemic inflammatory state . Although PCI‐focused AMI trials reported cerebrovascular event rates between ≈0.3% and 1%, stroke risks among AMI patients undergoing CABG range between 0.8% and 6% . We found a slightly although not statistically significant lower proportion of strokes in patients with STEMI compared with NSTEMI (2.0% versus 3.9%, P =0.134).…”
Section: Discussionmentioning
confidence: 50%
“…16 Although PCI-focused AMI trials reported cerebrovascular event rates between 0.3% and 1%, stroke risks among AMI patients undergoing CABG range between 0.8% and 6%. [3][4][5] We found a slightly although not statistically significant lower proportion of strokes in patients with STEMI compared with NSTEMI (2.0% versus 3.9%, P=0.134). The causes underlying perioperative strokes are multifactorial and thus difficult to modify.…”
Section: Lower Stroke Rate and Fewer Bleeding Complications In Stemi mentioning
confidence: 55%
See 2 more Smart Citations
“…Two observational studies from 2010 both reported equivalent in-hospital mortality and 30-day mortality rates irrespective of the timing of CABG from admission for NSTE-ACS [28,29]. A more recent study by Davierwala et al [30] analyzed 750 patients over a 5-year period and showed similar in-hospital mortality and 5-year mortality rates among NSTE-ACS patients who underwent CABG in less than 24, 24–72 h, versus more than 72 h after symptom onset. However, NSTE-ACS practice guidelines highlight certain conditions that should prompt urgent revascularization including cardiogenic shock, refractory ischemia despite optimal medical therapy, sustained ventricular arrhythmias, or dynamic ST-segment changes accompanying ischemic symptoms [4].…”
Section: Utilization Of Cabg For Nste-acsmentioning
confidence: 99%